Artful dodgers reconceiving the golden age of children's literature - Gubar, Marah, 1973- (Oxford : Oxford University Press, 2009)
In this account of the Golden Age of children's fiction, Gubar redefines the phenomenon known as the 'cult of the child'. She looks at the works of Lewis Carroll, Frances Hodgson Burnett and J. M. Barrie, contending that they reject the simplistic 'child of Nature' paradigm in favor of one based on the child as an artful collaborator.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Children's literature, English -- History and criticism; English literature -- 19th century -- History and criticism; Children in literature; Adolescence in literature